2019
DOI: 10.22452/ajba.vol12no1.8
|View full text |Cite
|
Sign up to set email alerts
|

Inflation Hedging Properties of Different Asset Classes in Malaysia

Abstract: Manuscript type: Research paper Research aims: The objective of this study is to examine the inflation hedging properties of various asset classes (stock, gold, real estate, Treasury bond and Treasury bill) in the Malaysian context. Design/Methodology/Approach: This is an empirical analysis using quarterly data from the period of 1980 to 2016. The Autoregressive Distributed Lag (ARDL) bounds cointegration model is used for testing the long-run relationship while the error correction model (ECM) is used for tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 53 publications
1
4
1
Order By: Relevance
“…The results obtained contradict some studies (e.g. : Fama, Schwert, 1977;Lee, Isa, 2019;Choi, Shin, 2022). However, as noted by researchers, different research methods may produce different results (Bond, Seiler, 1998;Arnold, Auer, 2015;Aye, Chang, Gupta, 2016).…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…The results obtained contradict some studies (e.g. : Fama, Schwert, 1977;Lee, Isa, 2019;Choi, Shin, 2022). However, as noted by researchers, different research methods may produce different results (Bond, Seiler, 1998;Arnold, Auer, 2015;Aye, Chang, Gupta, 2016).…”
Section: Discussioncontrasting
confidence: 57%
“…For example, cointegration tested by the Engle-Granger test did not allow such conclusions to be drawn. Lee and Isa (2019) Trojanek (2007) analysed the relationship of residential real estate prices in Poznan between 1996 and 2004 by examining the relationship in relation to expected and unexpected inflation. The research showed that real estate can effectively hedge capital against inflation.…”
Section: Literature Overviewmentioning
confidence: 99%
“…The study was conducted from Q1 1999 to Q4 2015, resulting in a total of 68 observations. The Malaysian market was also studied by Lee and Isa (2019) however extending their study to other asset classes such as stocks, bonds and gold. They obtained results that, while stocks and government bonds provide a hedge against inflation, real estate provides only a partial hedge.…”
Section: Literature Overviewmentioning
confidence: 99%
“…Shifting the focus to Hong Kong's property market, Lee (2013) demonstrated the cointegration of residential property market returns and inflation between 1980 and 2008, with changes in inflation preceding changes in property returns. The analysis of the Malaysian market indicated that real estate provides only a partial hedge against inflation and it is more advisable to invest in stocks and government bonds (Lee et al, 2019).…”
Section: Literature Review and Research Purposementioning
confidence: 99%